A Peptide/MHCII conformer generated in the presence of exchange peptide is substrate for HLA-DM editing - Ferrante, Andrea (Nature Publishing Group, 2012)
The mechanism of HLA-DM (DM) activity is still unclear. We have shown that DM-mediated peptide release from HLA-DR (DR) is dependent on the presence of exchange peptide. However, DM also promotes a small amount of peptide release in the absence of exchange peptide. Here we show that SDS-PAGE separates purified peptide/DR1 complexes (pDR1) into two conformers whose ratio is peptide K(d)-dependent. In the absence of exchange peptide, DM only releases peptide from the slower migrating conformer. Addition of exchange peptide converts the DM-resistant conformer to the slower migrating conformer, which is DM labile. Thus, exchange peptide generates a conformer of pDR1 which constitutes the intermediate for peptide exchange and the substrate for DM activity. The resolution of the intermediate favors the highest affinity peptide. However, once folded into the DM-resistant conformer, even low affinity peptides can be presented in the absence of free peptide, broadening the repertoire available for presentation.